2017
DOI: 10.29252/johe.6.2.98
|View full text |Cite
|
Sign up to set email alerts
|

Mental workload and its association with fatigue in operating room personnel of Hamadan hospitals, Iran, 2016

Abstract: Received: May 2017, Accepted: July 2017 Background: Fatigue in the workers reduces the individual's resistance and eventually leads to the lower performance, increased errors and accidents. This study assessed the fatigue, mental workload and the correlation between them, in operating room personnel of Hamadan hospitals, Iran. Materials and Methods: In a descriptive study, the mental workload and its association with fatigue in operating room personnel were investigated. Total of 188 cases including surgeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…On the other hand, the current study results showed a significant correlation between psychological workload based on the P-JCQ and various types of fatigue derived from the P-SOFI, which was inconsistent with the study results performed by Arellano et al [53]. However, Motamedzade et al [54] and Fan et al [55] reported a significant association between psychological workload and occupational fatigue.…”
Section: Potential Factors Associated With Various Types Of the Occup...contrasting
confidence: 99%
“…On the other hand, the current study results showed a significant correlation between psychological workload based on the P-JCQ and various types of fatigue derived from the P-SOFI, which was inconsistent with the study results performed by Arellano et al [53]. However, Motamedzade et al [54] and Fan et al [55] reported a significant association between psychological workload and occupational fatigue.…”
Section: Potential Factors Associated With Various Types Of the Occup...contrasting
confidence: 99%
“…Mirzaei Tusi et al [ 51 ] showed that the mental fatigue was significantly associated with the mental workload. On the other hand, some studies in healthcare personnel have stated that there is no relationship between mental workload and occupational fatigue [ 34 , 35 ]. This difference can be due to various reasons, including the difference in the nature of tasks in different jobs.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it can be assumed that fatigue can indirectly mediate the relationship between mental workload and job performance. On the other hand, some studies in healthcare personnel have stated that there is no relationship between mental workload and occupational fatigue [ 34 , 35 ]. According to the background presented above, the mediating effect of fatigue on mental workload and job performance is not well known.…”
Section: Introductionmentioning
confidence: 99%
“…Job dissatisfaction, mental disorders, lack of sleep and workload are fatigue risk factors in the job (Motamedzade et al, 2017). Table 3 shows that most of the respondents had a heavy mental workload (61-80).…”
Section: Mental Workloadmentioning
confidence: 99%
“…The results of the group comparison show that a higher mental workload contributes to exposure to Coronavirus Disease of 2019 . Based on the research of Motamedzade et al (2017) it was concluded that mental workload correlates with fatigue in nurses in the operating room. Therefore, reducing mental workload can reduce fatigue in nurses.…”
Section: Introductionmentioning
confidence: 99%